Clinical outcomes of restricted kinematic alignment versus mechanical alignment in total knee arthroplasty: a meta-analysis of randomized controlled trials - Xiao-peng Gao; Miao Zhang; Zi-yi Zhang; Xiao-tong Li (BMC Musculoskeletal Disorders)
Abstract Background Restricted Kinematic Alignment (rKA) is a well-established technique for total knee arthroplasty (TKA) that aims to approximate natural knee motion within defined safety boundaries. This meta-analysis aims to evaluate the clinical efficacy of rKA compared to mechanical alignment (MA) in TKA. Method A comprehensive search was conducted in the PubMed, Embase, Web of Science, and Cochrane Library databases for randomized controlled trials (RCTs) published from the inception of these databases until December 6, 2024. RCTs assessing the clinical efficacy of rKA and MA in TKA were included. A total of six RCTs were analyzed. Results A total of six RCTs involving 444 patients were included in the analysis. The meta-analysis revealed that the Knee Society Score (KSS) and McMaster Universities Osteoarthritis Index (WOMAC) scores were significantly higher in the rKA group compared to the MA group. However, no significant differences were found between the rKA and MA groups in terms of the Oxford Knee Score (OKS), Knee Injury and Osteoarthritis Outcome Score (KOOS), Forgotten Joint Score (FJS), hip-knee-ankle angle (HKA), and lateral distal femoral angle (LDFA). Additionally, the postoperative revision rate in the rKA group was not significantly different from that in the MA group. Conclusion This study suggests that rKA provides better functional outcomes in TKA compared to MA, particularly in terms of WOMAC score and KSS. Clinical trial number Not applicable.